Optimasi Kinerja Pencahayaan Alami melalui Rancangan Courtyard Well dan Bukaan Cahaya pada Rusunawa Cingised Blok 4 - Putri, Ghea Helena Firmansyah; Sahid (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2025)
Title: Daylighting Performance Optimization Through Courtyard Well and Window Opening Design at Rusunawa Cingised Blok 4 Low-rise apartments have emerged as a viable solution as the need for low-income housing grows and land becomes scarce. In the 2024 building type design of low-rise flats, courtyards were included to improve daylighting performance. However, observations show that daylighting in low-rise public housing, such as Cingised Block 4, is still not optimal, requiring evaluation and optimization. This study examines the effect of the courtyard well’s geometric proportions, considering the horizontal obstruction from the single-loaded corridor surrounding the courtyard well. The research aims to determine the impact of optimal courtyard well configurations and light openings on natural lighting performance in Cingised Block 4 low-rise apartments. The study employs evaluative and comparative methods with a quantitative approach through digital simulation. The simulation uses the Radiance Ray Tracing system for daylight metrics based on Climate-Based Daylight Modelling and utilizes LightStanza software. The optimization results for Cingised Block 4 show that increasing the width dimensions of the courtyard well and the Plan Aspect Ratio variable will enhance the daylight quantity despite the corridor overhang. Optimizing the facade configuration of apartment units facing the courtyard well through the Window Wall Ratio (WWR) can significantly improve the distribution and quantity of daylight in the rooms.